Implementation of Life Skills Learning in Developing Entrepreneurship Attitude of Students in SKB Purwokerto - Mursita, Denys Agis; Suminar, Tri (Journal of Nonformal Education and Community Empowerment, 2019)
This study aims to describe life skills learning in building entrepreneurial attitude of learning citizens of C package in SKB Purwokerto. This type of research is qualitative descriptive. Research subjects were 2 studying residents and 2 tutors as well as 1 informant that is package manager C. data collection technique through observation, interview, and documentation. The validity of the data using source and method triangulation. Data analysis techniques through data collection, data reduction, data presentation, and conclusions. Life Skills study results are conducted in accordance with the Life Skills learning component and generate entrepreneurial attitudes in the form of self-confidence, task-oriented and result oriented, risk-taking, leadership, originality, and future-oriented. Constraints faced in the form of internal factors namely learning motivation and external factors that is the environment. Supporting factors in this learning is the availability of facilities and complete infrastructure and competence of tutors in accordance with the type of skills taught.